1997
DOI: 10.1007/s002329900292
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic Regulation of Na + Transport Across A6 Epithelium: Interactions with Prostaglandin E 2 and Cyclic AMP

Abstract: Previous work from this laboratory has shown that apical membrane sodium channel activity is stimulated by serosal hyposmotic solutions (Wills, Millinoff & Crowe, 1991). In the present study, we determined whether this stimulation of sodium transport is additive with the actions of prostaglandin E2 (PGE2) or cyclic AMP (cAMP). Addition of exogenous PGE2 (100 nM; serosal bath) to isosmotic solutions led to large increases in the amiloride-sensitive short-circuit current (Isc) and transepithelial conductance (Gt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 25 publications
3
12
0
Order By: Relevance
“…Previous studies have shown that amiloride-sensitive Na ϩ transport in A6 cells and native tissues is controlled by products of the enzyme PLA 2 (12)(13)(14)(15). Our results in Xenopus oocytes expressing ␣␤␥ mENaC confirm and extend these observations.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Previous studies have shown that amiloride-sensitive Na ϩ transport in A6 cells and native tissues is controlled by products of the enzyme PLA 2 (12)(13)(14)(15). Our results in Xenopus oocytes expressing ␣␤␥ mENaC confirm and extend these observations.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, the addi-tion of blockers of PLA 2 or cyclooxygenase to the basolateral bath inhibited transepithelial Na ϩ transport. This decrease in Na ϩ transport was reversed by prostaglandin E 2 (14,15).…”
mentioning
confidence: 95%
“…Moreover, it was shown that infusion of prostaglandins in renal tubular fluid can increase Na ϩ reabsorption (3). Addition of exogenous PGE 2 to isosmotic solutions led to large increases in the amiloride-sensitive I sc and transepithelial conductance in A6 cells (25). PGE 2 also stimulates sodium reabsorption in MDCK-C7 cells (52).…”
Section: Discussionmentioning
confidence: 99%
“…As demonstrated in Fig. 1, mpkCCD thermore, PGE 2 under certain circumstances enhances ENaC activity in A6 (19,25) and Madin-Darby canine kidney (MDCK) cells (52). Thus we examined whether inhibition of cyclooxygenase (COX) with COX-selective nonsteroid antiinflammatory agents such as diclofenac and ibuprofen would alter ENaC-mediated sodium transport in mpkCCD c14 cells.…”
Section: Identification Of Cyp Metabolites Of Aa In Mpkccd C14 Cellsmentioning
confidence: 99%
“…In A6 cell monolayers, hypotonic stress induces Na ϩ transport immediately (within 10 min) after application of the stress (18,24,26,27,29,37). Several studies revealed that hypotonic stress has a genomic and a nongenomic impact on Na ϩ reabsorption (26,29,33,37).…”
mentioning
confidence: 99%